2020
DOI: 10.1155/2020/9232138
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Seismic Behavior of a Steel‐Concrete Hybrid Structure with Buckling Restrained Braces

Abstract: e damage to a concrete wall caused by a strong earthquake is generally concentrated at the bottom of the concrete wall, which seriously threatens the safety of the steel-concrete hybrid structure and is very difficult to repair after an earthquake. In this paper, a steel-concrete hybrid structure with buckling restrained braces at a scale of 1/10 is constructed and tested on a shaking table. First, the mechanical properties of the BRBs are obtained through a static reciprocating loading test. en, the dynamic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Li et al [2] resulted that damage to a concrete wall generated by a major earthquake is typically concentrated near the bottom of the wall, posing a serious threat to the steel-concrete hybrid structure's safety and making earthquake rehabilitation extremely difficult. A steelconcrete hybrid structure with buckling restrained bracing is built and tested on a shaking table at a size of 1/10 in this study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li et al [2] resulted that damage to a concrete wall generated by a major earthquake is typically concentrated near the bottom of the wall, posing a serious threat to the steel-concrete hybrid structure's safety and making earthquake rehabilitation extremely difficult. A steelconcrete hybrid structure with buckling restrained bracing is built and tested on a shaking table at a size of 1/10 in this study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li et al 14 set magnetorheological dampers in an SFRCCS to reduce the structural damage and experimentally validated the seismic control capacity of the new system. Li et al 15 installed buckling restrained braces in the SF of an SFRCCS to change the distribution of cracks in the reinforced concrete core. Shaking table test results of a 10‐story specimen showed that after installing buckling restrained braces, the cracks in the reinforced concrete core were widely distributed in stories 1–8, and the SF was basically in an elastic state under major earthquakes.…”
Section: Introductionmentioning
confidence: 99%